Reconstruction left atrium and isolation pulmonary veins of paroxysmal atrial fibrillation using single contact force catheter with zero x-ray exposure: A CONSORT Study. Issue 41 (October 2017) - Zhang, Jian Qiang; Yu, Rong Hui; Liang, Jia Bing; Long, De Yong; Sang, Cai Hua; Ma, Chang Sheng; Dong, Jian Zeng
Abstract: Background: Conventional ablation of paroxysmal atrial fibrillation (PAF) is associated with radiation risks for patients and laboratory staff. Three-dimensional (3D) mapping system capable of showing contact force (CF) and direction of catheter tip may compensate for nonfluoroscopic safety issues. Objective: The aim of this study was to investigate the feasibility of zero x-ray exposure during reconstruction left atrium (LA) and ablation. Methods: Single, CF catheter, and 3D mapping system were used to reconstruct LA and isolate pulmonary veins (PV) in all patients. The patients were randomly divided into 2 groups after LA angiography. In group 1, reconstruction LA and isolation PV was performed with the help of 3D system (without x-ray), whereas in group 2, x-ray and 3D system were utilized to reconstruct LA and ablate PV antrum. After ablation, Lasso catheter was used to confirm the PV isolation. All patients were followed up to 12 months. Results: A total of 342 PAF patients were continuously enrolled. The basic clinical characteristics between the 2 groups had no significant difference. Parameters related to the procedure, average procedure time, ablation procedure time, average contact force (CF) applied, the percentage of time within CF settings, and average power applied during radiofrequency application showed no significant difference between the 2 groups. In group 1, the average fluoroscopy time before LA reconstruction was similar to that in group 2 (2.8 ± 0.4 vs. 2.4 ± 0.6 minutes, P  = .75). The average fluoroscopy time during ablation was significantly lower than that in group 2 (0 vs. 7.6 ± 1.3 minutes, P  < .001). The total x-ray exposure dose of the procedure in group 1 was significantly lower than that in group 2 (19.6 ± 9.4 vs. 128.7 ± 62.5 mGy, respectively, P  < .001). Kaplan-Meier analysis indicated that there were no statistical differences in the probability of freedom from atrial arrhythmia (AF/AFL/AT) recurrence at 12 months between group 1 and group 2 ( P  = .152). The success rate after a single ablation procedure and without drugs (Class I/III AAD) at 12 months was not significantly different between the 2 groups (67.6%, 95% confidence interval [CI]: 62%–79.5% in group 1 and 68.9%, 95% CI: 63%–80.7% in group 2, P  = .207). Procedural-related adverse events showed no significant different incidence between group 1 and group 2. A multivariate logistic regression analysis of risk factors was performed to evaluate the effectiveness outcome, which demonstrated that the percentage of CF (within the investigator-selected work ranges) during therapy was significantly associated with positive outcomes (odds ratio: 3.68; 95% CI: 1.65–10.6, P  = .008), whereas the LA dimension was negatively associated with effectiveness outcomes (odds ratio: 0.72; 95% CI: 0.52–0.84, P  = .016). Conclusions: Reconstruction LA and isolation PV ablation using single CF-assisted catheter without x-ray exposure was both safe and effective. CF was positively associated with effective outcomes and LA dimensions negatively with effective ones.